Explaining the recent decrease in coronary heart disease mortality rates in Ireland, 1985–2000. Issue 4 (13th March 2006) - Bennett, Kathleen; Kabir, Zubair; Unal, Belgin; Shelley, Emer; Critchley, Julia; Perry, Ivan; Feely, John; Capewell, Simon
Abstract : Study objectives: To examine the proportion of the recent decline in coronary heart disease (CHD) deaths in Ireland attributable to (a) "evidence based" medical and surgical treatments, and (b) changes in major cardiovascular risk factors. Design setting: IMPACT, a previously validated model, was used to combine and analyse data on the use and effectiveness of specific cardiology treatments and risk factor trends, stratified by age and sex. The main data sources were published trials and meta-analyses, official statistics, clinical audits, and observational studies. Results: Between 1985 and 2000, CHD mortality rates in Ireland fell by 47% in those aged 25–84. Some 43.6% of the observed decrease in mortality was attributed to treatment effects and 48.1% to favourable population risk factor trends; specifically declining smoking prevalence (25.6%), mean cholesterol concentrations (30.2%), and blood pressure levels (6.0%), but offset by increases in adverse population trends related to obesity, diabetes, and inactivity (−13.8%). Conclusions: The results emphasise the importance of a comprehensive strategy that maximises population coverage of effective treatments, and that actively promotes primary prevention, particularly tobacco control and a cardioprotective diet.